2016
DOI: 10.3928/01477447-20160623-03
|View full text |Cite
|
Sign up to set email alerts
|

Patient Perceptions of Reimbursement for Arthroscopic Meniscectomy and Anterior Cruciate Ligament Reconstruction

Abstract: Historically, patient perceptions of surgeon reimbursement have been exaggerated compared with actual reimbursement. There is limited information about patient perceptions of physician reimbursement for arthroscopic meniscectomy and anterior cruciate ligament (ACL) reconstruction. This study evaluated patient perceptions of physician reimbursement for these procedures and compared perceptions of health care reform between urban and suburban clinics. Surveys were given to 231 consecutive patients, and patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…Furthermore, when told the actual amount of compensation, patients felt their surgeon should have received higher pay for their services. 1,2 Similar results were found in other specialties with patients undergoing plastic surgery estimating that their surgeons received anywhere from 290 to 1061 per cent of their actual reimbursement. 3 Likewise, patients who underwent minimally invasive general surgical procedures predicted that Medicare reimbursements were about 10 times higher than the actual payout.…”
supporting
confidence: 71%
See 2 more Smart Citations
“…Furthermore, when told the actual amount of compensation, patients felt their surgeon should have received higher pay for their services. 1,2 Similar results were found in other specialties with patients undergoing plastic surgery estimating that their surgeons received anywhere from 290 to 1061 per cent of their actual reimbursement. 3 Likewise, patients who underwent minimally invasive general surgical procedures predicted that Medicare reimbursements were about 10 times higher than the actual payout.…”
supporting
confidence: 71%
“…5 The few studies that have looked at surgeon reimbursement are limited to either general, bariatric, orthopedic, or plastic surgery procedures. [1][2][3][4][5][6][7][8] There are no published studies that specifically address patients undergoing complex index surgical oncology procedures. As surgery continues to become more specialized with physicians seeking additional years of training, investigations should be made into the reimbursement for different specialized branches of general surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies from other specialties consistently demonstrate similar results that patients overestimate physician payments. [4][5][6][7][8] For example, a recent study demonstrated that patients estimate costs for meniscectomy 14 times higher and anterior cruciate ligament repair 11 times higher than actual reimbursement. 8 In our study, patients also overestimated surgeon's fees for CABG and appendectomy, which have been used as controls.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8] For example, a recent study demonstrated that patients estimate costs for meniscectomy 14 times higher and anterior cruciate ligament repair 11 times higher than actual reimbursement. 8 In our study, patients also overestimated surgeon's fees for CABG and appendectomy, which have been used as controls. Our study was based on a paper from the orthopedic literature, which also reported patient perceptions on costs of CABG and appendectomy, and interestingly, we found strikingly similar results.…”
Section: Discussionmentioning
confidence: 99%